Analysis of the Genomes and Adaptive Traits of Skermanella cutis sp. nov., a Human Skin Isolate, and the Type Strains Skermanella rosea and Skermanella mucosa - Yujin Choi; Munkhtsatsral Ganzorig; Kyoung Lee (Microorganisms)
The genus Skermanella comprises important soil bacteria that are often associated with the crop rhizospheres, but its physiological traits remain poorly understood. This study characterizes Skermanella sp. TT6T, isolated from human skin, with a focus on its metabolic and environmental adaptations. Genome sequencing and phylogenomic analyses revealed that the strain TT6T is most closely related to S. rosea M1T, with average nucleotide identity and digital DNA–DNA hybridization values of 94.14% (±0.5%) and 64.7%, respectively. Comparative genomic analysis showed that the strains TT6T, S. rosea M1T and S. mucosa 8-14-6T share the Calvin cycle, and possess photosynthetic genes associated with the purple bacteria-type photosystem II. The strains TT6T and S. rosea M1T exhibited growth in a nitrogen-free medium under microaerobic conditions, which were generated in test tubes containing 0.1% soft agar. Under these conditions, with nitrate as a nitrogen source, S. rosea M1T formed gases, indicating denitrification. Strain TT6T also contains gene clusters involved in trehalose and carotenoid biosynthesis, along with salt-dependent colony morphology changes, highlighting its adaptive versatility. Genomic analyses further identified pathways related to hydrogenase and sulfur oxidation. Phenotypic and chemotaxonomic traits of strain TT6T were also compared with closely related type strains, confirming its genotypic and phenotypic distinctiveness. The new species, Skermanella cutis sp. nov., is proposed, with TT6T (=KCTC 82306T = JCM 34945T) as the type strain. This study underscores the agricultural and ecological significance of the genus Skermanella.